PTH-007 Ercp Cannulation Success Benchmarking: Implications For Certification And Validation. (9th June 2014) - Sheppard, D; Craddock, S; Warner, B; Wilkinson, M
Abstract : Introduction: An investigation of success rates of cannulating a 'virgin' papilla during endoscopic retrograde cholangiopancreatography (ERCP) at a tertiary referral centre, compared against Joint Advisory Group (JAG) guidelines, and assessment of the reasons for failure. Methods: Retrospective review of Endosoft database and radiology records of patients who underwent ERCP conducted between 2006–2012 (n = 1519) at the Gastroenterology department, St Thomas' Hospital, London. Specifically 'virgin' papillae were considered, defined as those with no evidence of prior cannulation, stents in situ or sphincterotomies (n = 795), as these represent the most challenging and repeatable targets for endoscopists. Results: Over the 7 year period, the overall ERCP cannulation success rate per patient was 86, or 79% per virgin papilla procedure. By defining an 'accessible' (see Table) virgin papilla, a 90% success rate was achieved for each procedure, as well as per patient. Procedure success rates per consultant ranged from 79 – 89% for virgin, and 94 – 99% for non virgin cannulations, highlighting the need for careful definition of success criteria. Chronic pancreatitis was the only statistically significant indication associated with a failed cannulation (OR=3.3, CI: 1.7–6.4), and previous failure begat subsequent failure (OR=2.2, CI: 1.1- 4.4). Reasons for failure included previous gastroduodenal surgery (OR=48.9, CI: 6.3–379.2), papilla tumour impingement (OR=57.8, CI: 7.5–443.3), duodenal stricturing (OR=36.0, CI: 4.5 – 286.3). Conclusion: The 79% success rate for virgin papilla cannulation at a tertiary referral centre needs to be understood in context of JAG's recommended 80% success for overall therapeutic intent. As can be seen, depending on the way we define the duct, and therapeutic intent, we can fall short or far exceed the JAG guidelines. We believe that our data shows that the JAG benchmark for therapeutic success at initial attempt for trainees, and even for established ERCP-ists is currently too ambitious, since therapy requires cannulation to be achieved, and therapeutic success is not universal after successful diagnostic ERCP. We also believe that any measure of success needs to include the minimum criteria of whether the papilla was virgin, accessible, or associated with either previous failure or intended pancreatic therapy. As a corollary of this work we hope to encourage other units to publish clearer definitions when defining success. Disclosure of Interest: None Declared.